2021
DOI: 10.21203/rs.3.rs-778056/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the Intention to Receive the COVID-19 Vaccination in Macao: Implications for Vaccination Strategies

Abstract: Background: Understanding the intention of receiving COVID-19 vaccines is important to inform effective vaccination strategies. This study aimed to investigate such intention, identify the key influencing factors, and determine the most important intention predictors using a theoretically principled model. Methods: An online, cross-sectional survey method was implemented in Macao in May 2021. People aged 18 years or above and residing in Macao for 12 months prior to the study were recruited through social medi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“… 5 For example, cross-sectional surveys in the United States, Turkey, the UK, Brazil, Egypt, Sub-Saharan Africa and Italy show that the hesitation rate of the COVID-19 vaccine was 42.4% (in 2020), 6 45.3% (in 2021), 7 20.7% (in 2021), 8 10.5% (in 2020), 9 41.9% (in 2021), 10 49% (in 2021), 11 and 31.1% (in 2021), 12 respectively. Furthermore, studies have revealed that hesitancy of the COVID-19 vaccine is common among the general population in China 13 as hesitancy proportions were: 54.7% in Hong Kong (in 2020), 14 19.2% in Macao (in 2021), 15 35.5% in Beijing (in 2021), 16 and 41.2% in Southwest China (2021). 17 Vaccine hesitancy is an ongoing problem, and a better understanding of the phenomenon and its determinants in specific populations can develop more effective and targeted vaccination strategies.…”
Section: Introductionmentioning
confidence: 99%
“… 5 For example, cross-sectional surveys in the United States, Turkey, the UK, Brazil, Egypt, Sub-Saharan Africa and Italy show that the hesitation rate of the COVID-19 vaccine was 42.4% (in 2020), 6 45.3% (in 2021), 7 20.7% (in 2021), 8 10.5% (in 2020), 9 41.9% (in 2021), 10 49% (in 2021), 11 and 31.1% (in 2021), 12 respectively. Furthermore, studies have revealed that hesitancy of the COVID-19 vaccine is common among the general population in China 13 as hesitancy proportions were: 54.7% in Hong Kong (in 2020), 14 19.2% in Macao (in 2021), 15 35.5% in Beijing (in 2021), 16 and 41.2% in Southwest China (2021). 17 Vaccine hesitancy is an ongoing problem, and a better understanding of the phenomenon and its determinants in specific populations can develop more effective and targeted vaccination strategies.…”
Section: Introductionmentioning
confidence: 99%